2013
DOI: 10.1007/s00280-013-2249-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory studies of the novel cyclin-dependent kinase inhibitor dinaciclib (SCH 727965) in acute leukemias

Abstract: PurposeDinaciclib inhibits cyclin-dependent kinases 1, 2, 5, and 9 with a better therapeutic index than flavopiridol in preclinical studies. This study assessed the activity of dinaciclib in acute leukemia both in the clinic and in vitro.MethodsAdults with relapsed/refractory acute myeloid leukemia (n = 14) and acute lymphoid leukemia (n = 6) were treated with dinaciclib 50 mg/m2 given as a 2-h infusion every 21 days.ResultsMost patients had dramatic but transient reduction in circulating blasts; however, no r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 36 publications
(40 reference statements)
2
74
0
Order By: Relevance
“…Compared with flavopiridol, dinaciclib showed a superior therapeutic index in a preclinical setting (Parry et al, 2010). Preliminary pharmacokinetic data from clinical studies in solid tumors suggest that average dinaciclib concentrations of 82.3-184 nM can be achieved (Mita et al, 2014;Gojo et al, 2013). Using a large panel of glioma cell lines, we have demonstrated that CDK inhibitors effectively inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with flavopiridol, dinaciclib showed a superior therapeutic index in a preclinical setting (Parry et al, 2010). Preliminary pharmacokinetic data from clinical studies in solid tumors suggest that average dinaciclib concentrations of 82.3-184 nM can be achieved (Mita et al, 2014;Gojo et al, 2013). Using a large panel of glioma cell lines, we have demonstrated that CDK inhibitors effectively inhibit cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Parry et al (2010) also showed that dinaciclib inhibited cell proliferation and cell-cycle progression in multiple tumor cell lines across a broad range of tumor types with different genetic backgrounds and induced regression of established solid tumors in mouse models. Despite research advances, reports of randomized phase 2 trials of dinaciclib in solid tumors have been disappointing (Mita et al, 2014), with no significant response in patients with non-small cell lung cancer (Stephenson et al, 2014) or acute lymphoblastic leukemia (Gojo et al, 2013). In this study, we investigated the cellular responses to CDK inhibitors in a panel of glioma cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, the elimination of dinaciclib is even more rapid, with a half-life of less than 1 hour (48,58). In both humans and mice, the direct pharmacodynamic effects of dinaciclib, including inhibition of MCL1, induction of PARP cleavage, and inhibition of PHA-stimulated lymphocyte proliferation, are transient and correlate with plasma drug concentration (58,74,82). In our study, dinaciclib-dependent changes in type I IFN gene expression within the tumor were observed at 24 hours, but not 4 days after dosing (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…PD0332991 is a specific inhibitor of CDK4 and CDK6, is generally well tolerated, and has shown clinical activity (57)(58)(59)(60). SCH727965 (dinaciclib), a novel inhibitor of CDK1, -2, -5, and -9, showed superior activity and an improved therapeutic index compared with flavopiridol in laboratory models of solid and hematologic malignancies (61,62) and was the subject of intense investigation in numerous clinical trials (63)(64)(65). However, preliminary data did not show a dramatic response to these CDK inhibitors, suggesting that other deregulated pathways are contributing to the growth and survival advantages of aggressive MCL cells compared with normal cells (8,33,34).…”
Section: Targeting Underlying Cell-cycle Dysregulation In Mcl: Cdk Inmentioning
confidence: 99%